The Role of Corporate Governance to Combat Corruption in Joint Stock Companies in Kingdom of Saudi Arabia - Almohammadi, Mwaddah Sami (Journal of Economic, Administrative and Legal Sciences, 2021)
This study aimed to clarify the role of the board of directors and the auditor in monitoring the application of governance in joint-stock companies to achieve the goal of combating corruption, and the problem of the study is the complexity of the dual roles of the control process for both the board of directors and the auditor, in addition to the lack of legal studies in the Kingdom on this topic The study relied on the descriptive approach, and by using the applied approach to support it with the decisions issued by the Capital Market Authority, so that we can see the extent of its adequacy and effectiveness, and the study reached several conclusions, including: One of the most important responsibilities of the Board of Directors is to protect the company from conflict of interest, because it poses a threat to justice , Because it leads to deviations and irregularities that affect the credibility and transparency of the business issued by its members.According to the study, a number of issues were presented, including: The researcher agrees to create a strict and solid board of directors that prevents conflict of interest and its forms, the continuation of all its forms, the continuation of all its work with its provisions.
Keywords: governance; joint stock companies; anti-corruption; board of directors; auditor